Clinical implications of the innovations in the primary tumour and metastasis of the 8th edition of the TNM classification for lung cancer - Rami-Porta, Ramón; Eberhardt, Wilfried E. E. (Journal of Thoracic Disease; Vol 10, Supplement 22 (August 22, 2018): Journal of Thoracic Disease (The 4th International Joint Meeting on Thoracic Surgery, Barcelona, 2018), 2018)
The 8th edition of the tumour, node and metastasis (TNM) classification for lung cancer introduced two new categories to accommodate adenocarcinoma in situ (AIS)—Tis(AIS)—and minimally invasive adenocarcinoma—T1mi; subdivided T1 into T1a (≤1 cm), T1b (>1–2 cm) and T1c (>2–3 cm); and T2 into T2a (>3–4 cm) and T2b (>4–5 cm); reclassified tumours >5–7 cm as T3, and those >7 cm as T4; reclassified endobronchial location